Implications of SARS-CoV-2-associated myocarditis in the medical evaluation of athletes - Raukar, N. P.; Cooper, L. T. (Sports Health: A Multidisciplinary Approach, 2020)
Myocarditis is a known cause of death in athletes. As we consider clearance of athletes to participate in sports during the COVID-19 pandemic, we offer a brief review of the myocardial effects of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) through the lens of what is known about myocarditis and exercise. All athletes should be queried about any recent illness suspicious for COVID-19 prior to sports participation.